Antiviral activity of human hepatocytes and its regulation by cellular antioxidant systems - Sularea, Vasile Mihai (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Although several antiviral strategies have been developed in the last decade, hepatotropic viruses are still a significant public health burden, with more than 300 million people being affected worldwide. Hepatocytes, the primary cells of the liver, are the primary targets of hepatotropic viruses. Moreover, hepatotropic viruses, in particular hepatitis B and C viruses, can persist causing chronic viral hepatitis, where hepatocellular carcinoma is a common outcome. While research on the liver antiviral response has focused on immune cell involvement, less is known about the intrinsic antiviral activity of hepatocytes, the primary target of hepatotropic viruses. Development of antiviral strategies focusing on hepatocyte antiviral activity might, as shown by clinical trials using type III interferons, increase the efficacy of antiviral therapies. Therefore, studying and characterising the molecular mechanisms behind antiviral activity of hepatocytes can potentially lead to development of new antiviral therapies. Pathogen detection and activation of innate antiviral activity is required for the clearance of the virus. In this case, evolutionary conserved pathogen-associated molecular patterns (PAMPs) are recognised by germline encoded pattern recognition receptors (PRRs). Virus-derived RNA, which acts as a potent PRR in hepatotropic viral infections, is recognised by different PRRs, such as Toll-Like Receptor 3 (TLR3), Retinoic Acid-inducible Gene I-like receptors (RLRs) and double-stranded RNA-activated protein kinase (PKR). In our study, using human hepatoma cell lines and induced pluripotent stem cell (iPSC)-derived hepatocytes as primary human hepatocyte models, we first aimed to identify the PRRs activated by viral-like RNA. In this case, using double stranded RNA (dsRNA) such as polyinosinic:polycytidylic acid (poly I:C) which mimics viral RNA, we observed that RLRs and PKR, but not TLR3, are the main receptors involved in recognition of immunogenic RNA by hepatocytes. Immune response-dependent metabolism has been extensively studied in immune cells. Whether cellular metabolism is involved in the innate antiviral response in hepatocytes, which have demanding metabolic roles when compared to other cell types, is subject of this thesis. In our study, we observed that stimulation with transfected dsRNA decreased mitochondrial respiration and increased reactive oxygen species (ROS) production while inducing an antiviral state. ROS homeostasis, regulated by ROS production and antioxidant enzymes, is crucial for modulating cell signaling and avoiding cell damage during viral infection. However, the molecular mechanisms through which antioxidant enzymes are involved in the innate antiviral response are not fully understood. Therefore, we went on to explore how cellular antioxidants involved in controlling ROS and oxidative stress might influence the antiviral activity of the hepatocyte. Analysing publicly available datasets, we identified the antioxidant enzyme peroxiredoxin 4 (PRDX4) as a potential regulator of innate antiviral activity in hepatocytes. Decreasing PRDX4 expression resulted in increased IFN-mediated antiviral activity and pro-inflammatory cytokine production following dsRNA stimulation or hepatotropic viral infection in human hepatic models. These results were confirmed in other cell types, suggesting that the mechanism observed is conserved among different cell types. Cytoplasmic dsRNA activates RLRs and the downstream mitochondrial antiviral protein (MAVS), which aggregates and functions as a hub for the activation of transcriptional factors involved in inducing the antiviral state. In this case, we observed that PRDX4 silencing increased MAVS aggregation upon dsRNA stimulation. Taken together, our results highlight and explore the intimate link between innate antiviral activity and the cellular redox system in hepatocytes. We identified a novel role for PRDX4 in modulating the innate antiviral response. The molecular mechanisms through which PRDX4 deficiency increase innate antiviral activity remain to be defined.
APPROVED
Keywords: antiviral; liver; hepatocyte; innate; metabolism; mitochondria; ROS; antioxidant; peroxiredoxin; mavs; interferon; pro-inflammatory; cytokine